The effect of biased expectation of news media on persuasion in a government crisis: An application of Expectancy Violation Theory - KyuJin SHIM, (Institutional Knowledge at Singapore Management University, 2015)
The purpose of this study is to investigate how publics perceive news coverage of a government crisis based on their biased perception of news media. More specifically, this study applied Expectancy Violation Theory (EVT) and conducted an experimental study of 321 Korean participants through a 2 (message type: expectation-confirmed vs. expectation-disconfirmed message) X 2 (news media type: anti-government vs. pro-government) between-subject design. The results showed that participants were more likely to perceive an expectation-disconfirmed message as more impartial than an expectation-confirmed message when they perceived news media as favorable to the government. On the contrary, respondents were more apt to evaluate an expectation-confirmed message as fairer than an expectation-disconfirmed message when they perceived news media as unfavorable to the government. Theoretical and practical implications are further discussed.